An Attitude Approach to the Prediction of Entrepreneurship - Robinson, Peter B.; Stimpson, David V.; Huefner, Jonathan C.; Hunt, H. Keith (Entrepreneurship Theory and Practice, 1991)
Attitude is presented as a better approach to the description of entrepreneurs than either personality characteristics or demographics. The development and validation of the Entrepreneurial Attitude Orientation (EAO) scale are explained. Sixty-three undergraduates were used in developing and establishing the test-retest reliability of the EAO. Fifty-four entrepreneurs and fifty-seven non-entrepreneurs served as known groups in establishing the discriminant validity of the EAO. There was a significant difference between known groups for all four of the EAO subscales (achievement, personal control, innovation, self-esteem); all subscales but achievement entered into a stepwise discriminant function.